2021
DOI: 10.3390/app11199267
|View full text |Cite
|
Sign up to set email alerts
|

The Manning’s Roughness Coefficient Calibration Method to Improve Flood Hazard Analysis in the Absence of River Bathymetric Data: Application to the Urban Historical Zamora City Centre in Spain

Abstract: The accurate estimation of flood risk depends on, among other factors, a correct delineation of the floodable area and its associated hydrodynamic parameters. This characterization becomes fundamental in the flood hazard analyses that are carried out in urban areas. To achieve this objective, it is necessary to have a correct characterization of the topography, both inside the riverbed (bathymetry) and outside it. Outside the riverbed, the LiDAR data led to an important improvement, but not so inside the river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In both weir and no-weir scenarios, higher Manning's roughness coefficients are related with lower discharges. Increased roughness coefficients cause slower flow velocities and higher energy losses, resulting in lower discharge values.This relationship holds true for various fixed bed materials (Aqeel Al-Adill et al, 2015; [ 34 , 36 , 42 ]).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In both weir and no-weir scenarios, higher Manning's roughness coefficients are related with lower discharges. Increased roughness coefficients cause slower flow velocities and higher energy losses, resulting in lower discharge values.This relationship holds true for various fixed bed materials (Aqeel Al-Adill et al, 2015; [ 34 , 36 , 42 ]).…”
Section: Resultsmentioning
confidence: 96%
“…Under the bed slope of 1:200, the average values of the Manning roughness coefficient and discharge differ from those under the bed slopes of 1:500 and 1:300. The variation in average Manning roughness coefficient and discharge values between different bed slopes indicates the channel bed slope has a substantial influence on flow properties[ 42 , 46 ]. These findings illustrate the necessity of considering bed slope into account when evaluating and constructing channels, since it has an essential effect on the overall flow behaviors and performance of the system.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies in flood inundation modeling, such as Dimitriadis et al [40], Sharma and Regonda [91], and Papaioannou et al, [36,42], have examined the usage of variable roughness coefficient values, but the channel roughness values were assumed spatially homogeneous. Even fewer works in flood inundation modeling have examined the usage of variable spatial distributed roughness coefficient values for the river bed (e.g., [92]). It should be mentioned that based on F1 and F2 skill scores, the high roughness coefficient scenario provided slightly higher values than the fifth roughness coefficient scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Some study has suggested that a parameter of main importance is the roughness of the river channel and the banks. Here, the Manning coefficient is used as roughness parameter (Doncker et al, 2009;Garrote et al, 2021;Hameed & Ali, 2013). Therefore, in this study, we selected the Manning's roughness coefficients as the most sensitive parameter in the model, and then, should be used for the calibration.…”
Section: Model Calibrationmentioning
confidence: 99%